ANALISA PENGARUH HIDROFOIL DENGAN VARIASI PLANING HULL CHINE TERHADAP LAJU ALIRAN SPEEDBOAT - Arif Winarno; Muhammad Anggara Pratama (Fakultas Sains dan Teknologi Universitas Karimun, 2022)
A ship especially a fast ship with a small size when operated will experience a condition when the ship is stationary and moving at low speed, the fast ship (planing boat) has properties like a displacement hull. The problem that is often faced by ships so far is the problem of ship resistance or ship resistance. The ship's resistance can be reduced by varying the design of a slimmer hull shape and adding hydrofoil to the hull so that the friction of the hull with water can be significantly reduced. In principle, the greatest resistance of the ship lies in the surface area of ​​the skin of the hull under water or often called the wet surface area (WSA = Wetted Surface Area). This study aims to determine the effect of adding hydrofoil on the flow rate of variations in the number of chines. In carrying out this research the author uses the Computational Fluid Dynamic (CFD) method and the calculation uses the Savitsky method for the settlement of resistance from the research objectives. From the results of the analysis and simulations carried out on the ship model, the lowest resistance value in the planing hull 3 chine model the resulting resistance is 262.27 kN and with the addition of hydrofoil the resulting resistance is 254.43 kN with a difference ratio of 3.6% it can be concluded with the addition of hydrofoil for each number of chines, it shows a reduction in the value of resistance in each model of the ship that uses hydrofoil by showing that the resulting transition flow is smoother for each model from the front of the hull to the back of the hull.